(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article systematically examines the role of physical activity or exercise therapy in the prevention of fatty hepatosis (FH) and hepatitis. Based on clinical studies, epidemiological observations, and randomized controlled trials, the effects of physical activity on reducing hepatic steatosis, improving liver enzyme levels, preventing fibrosis progression, and lowering morbidity and mortality associated with liver diseases are analyzed. Furthermore, the clinical effectiveness of different types, intensities, durations, and doses of activity (measured in MET-minutes per week) is evaluated. The findings indicate that physical activity can be considered a preventive strategy for fatty hepatosis and hepatitis through its influence on inflammation, insulin sensitivity, lipid metabolism, and brain–liver interactions.